Patient involvement for improved patient safety: A qualitative study of nurses’ perceptions and experiences - Skagerström, Janna (Nurs Open, 2017)
AIM: To explore nurses’ perceptions and experiences of patient involvement relevant to patient safety. DESIGN: Qualitative design using individual semi‐structured interviews. METHODS: Interviews with registered nurses (n = 11) and nurse assistants (n = 8) were conducted in 2015–2016. Nurses were recruited from five different healthcare units in Sweden. The material was analysed using conventional content analysis. RESULTS: The analysis resulted in four categories: healthcare professionals’ ways of influencing patient involvement for safer care; patients’ ways of influencing patient involvement for safer care; barriers to patient involvement for safer care; and relevance of patient involvement for safer care. The nurses expressed that patient involvement is a shared responsibility. They also emphasized that healthcare provider has a responsibility to create opportunities for the patient to participate. According to the nurses, involvement can be hindered by factors related to the patient, the healthcare provider and the healthcare system. However, respondents expressed that patient involvement can lead to safer care and benefits for individual patients.